2024
DOI: 10.3389/fenvs.2024.1307840
|View full text |Cite
|
Sign up to set email alerts
|

Paulownia trees as a sustainable solution for CO2 mitigation: assessing progress toward 2050 climate goals

Hesham S. Ghazzawy,
Ahmed Bakr,
Abdallah Tageldein Mansour
et al.

Abstract: Due to the progressive climate change on our planet, scientists are interested in solving this issue since it threatens not only certain regions or countries but also the world’s ecosystems and economies. Therefore, minimizing carbon dioxide (CO2) emissions and reducing atmospheric levels are global priorities. Thus, it is necessary at this moment to develop an appropriate approach to reduce or stabilize CO2 levels in the atmosphere. However, CO2 capture projects are long-term, low-profitable, and high-risk en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 132 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…The Frontoio cultivar exhibited the highest N concentration (1.24%) in the leaves, whereas Picual contained the lowest N (0.79%). Many researchers have demonstrated that N is transported to fruits, and that leaf N content is decreased in “on” years 34 , 43 – 49 . The results revealed that the leaf N concentration of the cultivars was relatively lower than the critical N level (1.5%) 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The Frontoio cultivar exhibited the highest N concentration (1.24%) in the leaves, whereas Picual contained the lowest N (0.79%). Many researchers have demonstrated that N is transported to fruits, and that leaf N content is decreased in “on” years 34 , 43 – 49 . The results revealed that the leaf N concentration of the cultivars was relatively lower than the critical N level (1.5%) 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%